Exhibit depicts isolation, beauty of mesa - Morrow, Shannon (Raton, NM Raton Range, 1994)
Article about a Johnson Mesa exhibit on display in the Old Pass Gallery.
Newspaper article + Photograph of Robert Sloan and Patsy Shandera.
Master list item #: 39
File location is in the Raton file Cabinet
Keywords: Sloan, Robert (Doctor) -- Artist; Shandera, Patsy -- Old Pass Gallery Director; Old Pass Gallery; Art Shows; Photography; Art Exhibits; Johnson's Mesa; Raton, New Mexico